2000
DOI: 10.1086/313770
|View full text |Cite
|
Sign up to set email alerts
|

Enteropathogens in Adult Patients with Diarrhea and Healthy Control Subjects: A 1-Year Prospective Study in a Swedish Clinic for Infectious Diseases

Abstract: A 1-year prospective study was conducted to identify enteropathogens in adults with diarrhea (n=851) and in healthy control subjects (n=203) by use of conventional laboratory methods. Virulence factor genes for diarrheagenic Escherichia coli were detected by polymerase chain reaction. Enteropathogens were identified in 56% of patients and 16% of control subjects. The isolation rate was 65% for patients with symptoms for <1 week and for travelers; >1 pathogen was found in 11% of patients. The most frequent ente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
119
4
5

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 240 publications
(152 citation statements)
references
References 46 publications
11
119
4
5
Order By: Relevance
“…A short duration of symptoms prior to sampling and frequent bowel movements should provide a higher yield. The study identified Cryptosporidium among 1% of patients, Entamoeba histolytica in 0.8% of patients and Giardia intestinalis in 0.7% of patients; these rates were low in relation to a study reporting Giardia intestinalis in 2% and Cryptosporidium in 2% (15).…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…A short duration of symptoms prior to sampling and frequent bowel movements should provide a higher yield. The study identified Cryptosporidium among 1% of patients, Entamoeba histolytica in 0.8% of patients and Giardia intestinalis in 0.7% of patients; these rates were low in relation to a study reporting Giardia intestinalis in 2% and Cryptosporidium in 2% (15).…”
Section: Discussioncontrasting
confidence: 57%
“…The current study observed a higher prevalence of viral infection than studies conducted within industrialized countries, where rotavirus and norovirus were identified in less than 5% of patients (15,18). As well as reflecting an increased prevalence of viral infections, this may be attributed to increased utilization of sensitive detection methods (RT-PCR) within routine diagnostics involved in pathogen identification (19).…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…This low prevalence of healthy carriage in the community is in keeping with the most recent estimates in developed countries. 31 Ten patients acquired C. difficile during antibiotic therapy. Whether this acquisition was due to contamination from the home environment or to spore reactivation in the digestive tract cannot be determined from our study data.…”
Section: Discussionmentioning
confidence: 99%